2017
DOI: 10.1149/2.0801706jes
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Microelectrochemical Observations of Very Early Stage Pitting on Ferrite-Pearlite Steel in Chloride Solutions

Abstract: The initiation site and morphology during the early stage of pitting on AISI 1045 carbon steel that has a microstructure of primary ferrite and pearlite were investigated in boric-borate buffer solutions with and without NaCl at pH 8.0. The pits initiated by micro-scale polarization were in the pearlite only and not in primary ferrite. In situ real-time observations during the micro-scale polarization of pearlite in a boric-borate buffer solution with 100 mM NaCl indicated that the pits were polygonal or rod-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 45 publications
1
34
0
2
Order By: Relevance
“…32 To ascertain the distributions of alloying elements in the microstructures of as-Q and QT specimens, the FE-EPMA analysis was conducted. Figure 2 shows the CLSM reflectance image and the EPMA mappings of the as-Q specimen with a full martensitic structure.…”
Section: Resultsmentioning
confidence: 99%
“…32 To ascertain the distributions of alloying elements in the microstructures of as-Q and QT specimens, the FE-EPMA analysis was conducted. Figure 2 shows the CLSM reflectance image and the EPMA mappings of the as-Q specimen with a full martensitic structure.…”
Section: Resultsmentioning
confidence: 99%
“…No cathodic treatment was performed, and polarization began in the passive region at −0.1 V to inhibit the active dissolution of steel matrix. 36 The cathodic currents were initially measured. The open circuit potentials (OCPs) of the as-quenched specimen, 1 h tempered specimen, 15 h tempered specimen, and 10 h tempered specimen were −0.07 V, −0.09 V, 0.00 V, and 0.21 V, respectively.…”
Section: Journal Of the Electrochemical Societymentioning
confidence: 99%
“…It appears that the corrosion resistance of the steel matrix was lower than that of the carbides. Kadowaki et al conducted in situ observations during micro-scale polarization of the pearlite structure (ferrite and cementite lamellae) in a boricborate buffer solution containing 100 mM NaCl 36 and found that the cementite (iron carbide) acts as a barrier against the growth of the pits initiated in the ferrite lamellae. In addition to the above explanation, although there were many small carbides in the specimens tempered for at most 10 h, no pit was initiated on these specimens.…”
Section: Journal Of the Electrochemical Societymentioning
confidence: 99%
“…[21][22][23] Because localized corrosion can be stopped at an early stage in micro-scale polarization, a very small pit was obtained. 24 Analyzing the area near the pit initiation point allows the roles of inclusions and segregation of alloying elements in pit initiation to be elucidated.To gain a better understanding of the pitting mechanism at inclusions, the target area for microelectrochemical measurements must be selected carefully. The pit initiation behavior can be successfully analyzed by making a small electrode area with one or a few inclusions.…”
mentioning
confidence: 99%
“…[21][22][23] Because localized corrosion can be stopped at an early stage in micro-scale polarization, a very small pit was obtained. 24 Analyzing the area near the pit initiation point allows the roles of inclusions and segregation of alloying elements in pit initiation to be elucidated.…”
mentioning
confidence: 99%